Relationship Between Physical Activity and Motor Vehicle Crashes Among Older Adult Drivers - Amish Talwar; Thelma J. Mielenz; Linda L. Hill; Howard F. Andrews; Guohua Li; Lisa J. Molnar; David W. Eby; Marian E. Betz; David Strogatz; Carolyn DiGuiseppi (SAGE Publishing, 2019)
Background: There are approximately 42 million licensed drivers aged 65 years or older in the United States, who face unique age-related risks while driving. While physical activity affects several chronic conditions thought to be associated with motor vehicle crashes (MVCs), it is unclear if increased physical activity leads to fewer MVCs. This study explores whether self-reported vigorous and moderate physical activity is associated with MVCs in the previous year. Methods: Using cross-sectional data from the LongROAD study, a large multisite prospective cohort study of 2990 older adult drivers, we examined variables related to physical activity and performed a multivariate regression analysis to examine the association of physical activity health behaviors with self-reported MVCs. Results: Overall, 41.2% of participants reported vigorous and 69.6% of participants reported moderate exercise at least once per week. Eleven percent of participants reported at least 1 MVC in the previous year. Neither vigorous nor moderate physical activity was significantly associated with self-reported MVCs in the previous year. Select variables that were significantly associated with self-reported MVC included self-reported unsafe driving practices (odds ratio [OR] 1.55, confidence interval [CI] 1.05-2.29), and fall in the past 12 months (OR 1.46, CI 1.14-1.85). Conclusions: We were unable to detect a significant association between self-reported physical activity and MVCs in the past year among this group of older drivers. Use of objective measures of activity may better clarify this relationship.